Organizational Predictors of Women on Corporate Boards - Hillman, Amy J.; Shropshire, Christine; Cannella, Albert A. (Academy of Management Journal, 2007)
Women are increasing in number among corporations' boards of directors, yet their representation is far from uniform across firms. In this study, we adopted a resource dependence theory lens to identify organizational predictors of women on boards. We tested our hypotheses using panel data from the 1,000 U.S. firms that were largest in terms of sales between 1990 and 2003. We found that organizational size, industry type, firm diversification strategy, and network effects (linkages to other boards with women directors) significantly impact the likelihood of female representation on boards of directors.